Autonomic and vascular function testing in collegiate athletes following SARS-CoV-2 infection: an exploratory study - Luck, J. Carter; Blaha, Cheryl; Cauffman, Aimee; Gao, Zhaohui; Arnold, Amy C.; Cui, Jian; Sinoway, Lawrence I. (Frontiers in Physiology, 2023)
Recent studies suggest that SARS-CoV-2 infection alters autonomic and vascular function in young, otherwise healthy, adults. However, whether these alterations exist in young competitive athletes remains unknown. This study aimed to assess the effects of COVID-19 on cardiac autonomic control and vascular function in collegiate athletes who tested positive for COVID-19, acknowledging the limitations imposed by the early stages of the pandemic. Sixteen collegiate athletes from various sports underwent a battery of commonly used autonomic and vascular function tests (23 ± 9, range: 12 -44 days post-infection). Additionally, data from 26 healthy control participants were included. In response to the Valsalva maneuver, nine athletes had a reduced early phase II blood pressure response and/or reduced Valsalva ratio. A depressed respiratory sinus arrhythmia amplitude was observed in three athletes. Three athletes became presyncopal during standing and did not complete the ten-minute orthostatic challenge. Brachial artery flow-mediated dilation, when allometrically scaled to account for differences in baseline diameter, was not different between athletes and controls (10.0 ± 3.5% vs. 7.1 ± 2.4%, P = 0.058). Additionally, no differences were observed between groups when FMD responses were normalized by shear rate (athletes: 0.055 ± 0.026 %/s-1, controls: 0.068 ± 0.049 %/s-1, P = 0.40). Few atypical and borderline responses to autonomic function tests were observed in athletes following an acute SARS-CoV-2 infection. The most meaningful autonomic abnormality being the failure of three athletes to complete a 10-minute orthostatic challenge. These 2 This is a provisional file, not the final typeset article findings suggest that some athletes may develop mild alterations in autonomic function in the weeks after developing COVID-19, while vascular function is not significantly impaired.